1997
DOI: 10.3346/jkms.1997.12.4.340
|View full text |Cite
|
Sign up to set email alerts
|

CNS innervation of the urinary bladder demonstrated by immunohistochemical study for c-fos and pseudorabies virus

Abstract: The aim of the present study is to verify the functional and anatomical neural pathways which innervate the urinary bladder in the central nervous system of the rat. To identify the functional neural pathway, the urinary bladder was stimulated by infusing formalin for 2 h. Then, brain and spinal cord were dissected out and immunohistochemistry was done by using anti-c-fos antibody. Many c-fos immunoreactive (IR) neurons were identified in the telencephalic cortical areas and in several brainstem nuclei, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…We did not perform immunohistochemical characterization of LUT afferents within spinal cord regions but did observe a sparse but consistent innervation of superficial laminae in the dorsal horn, as expected for nociceptive projections and documented by electron microscopy ( Park et al, 2019 ). This innervation was sparse in comparison to several other regions but is not the only site of LUT nociceptive signaling in the L6-S1 cord ( Cruz et al, 1996 ; Park et al, 1997 ; Lagos and Ballejo, 2004 ). Moreover, many sensory projections in the medial collateral pathway of the L6-S1 cord express GFRα3, a feature of many TRPV1-positive nociceptors innervating the bladder ( Forrest and Keast, 2008 ; Forrest et al, 2013 ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…We did not perform immunohistochemical characterization of LUT afferents within spinal cord regions but did observe a sparse but consistent innervation of superficial laminae in the dorsal horn, as expected for nociceptive projections and documented by electron microscopy ( Park et al, 2019 ). This innervation was sparse in comparison to several other regions but is not the only site of LUT nociceptive signaling in the L6-S1 cord ( Cruz et al, 1996 ; Park et al, 1997 ; Lagos and Ballejo, 2004 ). Moreover, many sensory projections in the medial collateral pathway of the L6-S1 cord express GFRα3, a feature of many TRPV1-positive nociceptors innervating the bladder ( Forrest and Keast, 2008 ; Forrest et al, 2013 ).…”
Section: Discussionmentioning
confidence: 92%
“…Continuous cystometry evokes immediate early gene expression in putative local interneurons within the SDCom (Cruz et al, 1994;Wiedmann et al, 2020), which could be initiated by both bladder and urethra afferents during the voiding cycle. This region also contains interneurons involved in urethral rhabdosphincter regulation, identified following transsynaptic tracing (Nadelhaft and Vera, 1996;Park et al, 1997;Vizzard et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4A and B). It has been reported that the most remarkable change in c-fos expression after bladder irritation occur in the DCM and then SPN regions of the L6 spinal cord in the rat (Birder and de Groat, 1992;Cruz et al, 1994Cruz et al, , 1996Park et al, 1997). Birder and de Groat also reported that the number of c-fos-positive cells in the DCM was related to activation of both pelvic and pudendal nerves and that the number of c-fos-positive cells in the SPN and MDH corresponds to pelvic nerve and pudendal nerve activation, respectively.…”
Section: Figmentioning
confidence: 99%